2014
DOI: 10.11646/phytotaxa.156.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybe chuxiongensis, a new bluing species from subtropical China

Abstract: A new bluing species of Psilocybe in sect. Caerulescentes is described from subtropical China. It is closely related to P. cubensis but can be differentiated by the lack of an annulus and the buff-yellow to yellowish brown, hemispheric to hemispheric-convex pileus without an umbo or papilla. Phylogenetic analyses of ITS, nrLSU and combined rpb2-tef1-α datasets using maximum parsimony and Bayesian inference also indicate its uniqueness. The relationship with P. cubensis is well-supported by molecular data with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
3
0
1
Order By: Relevance
“…& Ram.-Guill., our inclusion of the South African P. natalensis and the more recently described Asian species P. chuxiongensis revealed that P. cubensis likely shares an MRCA with P. natalensis and not the Asian species. This is consistent with the African-origin hypothesis for P. cubensis and/or its progenitor proposed by Guzmán et al ( 52 ) and Froese et al ( 53 ) rather than the Asian-origin hypothesis suggested by the relationships to Asian species in the work of Ramírez-Cruz et al ( 34 ) and Ma et al ( 54 ). However, it should be noted that the sequences of P. natalensis and P. thaiaerugineomaculans are not derived from type specimens (which is also true for P. cubensis ), and so while the geographic implications remain, the taxonomic ones are uncertain.…”
Section: Discussionsupporting
confidence: 91%
“…& Ram.-Guill., our inclusion of the South African P. natalensis and the more recently described Asian species P. chuxiongensis revealed that P. cubensis likely shares an MRCA with P. natalensis and not the Asian species. This is consistent with the African-origin hypothesis for P. cubensis and/or its progenitor proposed by Guzmán et al ( 52 ) and Froese et al ( 53 ) rather than the Asian-origin hypothesis suggested by the relationships to Asian species in the work of Ramírez-Cruz et al ( 34 ) and Ma et al ( 54 ). However, it should be noted that the sequences of P. natalensis and P. thaiaerugineomaculans are not derived from type specimens (which is also true for P. cubensis ), and so while the geographic implications remain, the taxonomic ones are uncertain.…”
Section: Discussionsupporting
confidence: 91%
“…We additionally recovered P. chuxiongensis T. Ma & H.D. Hyde from Yunnan, China (Ma et al 2014) as a sister taxon to P. cubensis in our ITS tree (Supplementary Figure 3. These results suggest an Asian rather than African origin for the progenitor of P. cubensis .…”
Section: Discussionmentioning
confidence: 99%
“…Una especie íntimamente relacionada, morfológica y filogenéticamente, es P. chuxiongensis Ma T. Ma & K. D. Hyde, pero se diferencia por la ausencia de anillo, y el píleo convexo, no papilado (Ma et al, 2014). Otras dos especies descriptas para el sudeste asiático P. aerugineomaculans (Höhnel) Singer y P. subaeruginascens Höhnel (= Stropharia caerulescens S. Imai), se asemejan por la presencia de un estípite con anillo membranáceo, pero se diferencian por sus esporas de menor tamaño (8,5-10 × 7-8 × 5,5-6,5 µm en P. aerugineomaculans) y 7,7-10 × 7-7,8 × 6-7 µm en P. subaeruginascens) y habito cortícola en el primer caso (Singer y Smith, 1958).…”
Section: Methodsunclassified